ANALYSIS SUPPLY CHAIN AND MARKETING OF ARABICA COFFEE REJANG LEBONG - Lestari, Fitri; Gabrienda, Gracia (Corolla International Conference, 2022)
Coffee is one of the leading commodities in Rejang Lebong Regency. Arabica coffee is one of the coffee commodities that is being intensively developed in Rejang Lebong Regency. The trade system for agricultural products is closely related to the income earned by farmers. It is against this background that coffee farmers as producers must quickly adapt to novelty and have innovations in marketing their agricultural products. Therefore, it is necessary to conduct research on the chain analysis of Arabica coffee trade and marketing in Rejang Lebong Regency. The implementation of this study aims to analyze the chain of trade and marketing of Arabica coffee beans in Rejang Lebong Regency. In addition, for knowing what factors influence Arabica coffee farmers in marketing their products.This research was conducted in 2 sub-districts, Curup Tengah and Selupu Rejang. This location was chosen purposively. processing data using the Analytic Hierarchy Process (AHP) program to knowing the value of the factors that influence the marketing of Arabica coffee beans. From the research, it can be seen that there are 2 Arabica coffee trading chains in Rejang Lebong Regency. In addition, the factors that determine the appropriate marketing channels selected by coffee farmers is influenced by several factors, namely: the amount of production (0.4244), quality (0.3873), price (0.1955), existence of ground coffee processing industry (0.0365).